PERAN LINGKUNGAN KERJA PADA PRODUKTIVITAS KARYAWAN SEBUAH STUDI ANALISIS - MG Supeni (PARAMETER, 2020)
This review aims to provide an indication of the current situation and irregularities that occur in the work environment and its impact on employee performance. Explanatory clues about borderline issues such as measuring positive and negative change in the work environment and employee satisfaction continuously influence employee productivity. Methodology: This study interprets the existing work environment in relation to workload and employee satisfaction. The study relies on a data set involving a variety of experiences and knowledge as well as the current situation in Bekasi. This review is expected to inspire readers to inspire further output in this field. Findings: This study provides an overview of a strategic orientation within existing research lines, helping to advise readers on what to know, what to know, and gaps for further investigation. Value: This study offers an overview of the latest understanding of these concepts in the field of human resource utility.